Investigation of the factors affecting the performance of employees performing physical work in the hospitality sector - Keresztes, Sándor; Hágen, István Zsombor (Acta Carolus Robertus, 2023)
The application of key performance indicators plays an important role in the field of work, business, education, and even sports and healthcare in order to monitor the process of achieving goals. Poorly defined indicators and metrics can generate unwanted partial results, results or side effects during the processes, which can reduce the success of individuals and organizations and, last but not least, can stand in the way of their development.In most countries of Europe, but in terms of the research target area, it can definitely be stated that the lack of skilled labor is a current and not negligible problem. Based on the experience of the past years, it is increasingly difficult to find a reliable, loyal employee who performs his profession at an appropriate level. In the case of foreign workers, inadequate knowledge of the German language causes additional difficulties for both employees and employers. My goal is to define a performance measurement system for manual workers, during which manual workers will be able to give the best of their knowledge, exceed expectations and become interested in the implementation of the employer's vision and business plans, so that their personal development is also ensured. This results in a cooperation during which the organization will be able to achieve the greatest possible efficiency with the existing number of employees. This alleviates the ever-increasing shortage of skilled labor.
Keywords: performance; efficiency; caterind industry; controlling; business